Case Report: Cerebrospinal Fluid Dynamics in the Optic Nerve Subarachnoid Space and the Brain Applying Diffusion Weighted MRI in Patients With Idiopathic Intracranial Hypertension—A Pilot Study - Berberat, Jatta; Pircher, Achmed; Gruber, Philipp; Lovblad, Karl-Olof; Remonda, Luca; Killer, Hanspeter Esriel (Frontiers in Neurology, 2022)
Purpose The aim of this study was to examine the cerebrospinal fluid (CSF) flow rates in the subarachnoid space (SAS) of the optic nerve (ON) and the brain in patients with idiopathic intracranial hypertension (IIH) and papilledema (PE) compared to healthy controls by applying non-invasive diffusion-weighted MRI. Methods A retrospective analysis of diffusion-weighted MR images of 5 patients with IIH (10 ONs), mean age: 31 ± 10 years (5 women), and 11 healthy controls (22 ONs, mean age: 60 ± 13 years, 5 women) was performed. The flow velocity flow-range ratio (FRR) between the intracranial cavity and the SAS of the ON was calculated in both groups and then compared. Results The mean FRR was 0.55 ± 0.08 in patients with IIH and 0.63 ± 0.05 in healthy controls. The difference between patients with IIH and healthy controls was statistically significant (p < 0.05). Conclusions The CSF flow velocity was decreased in patients with IIH with PE compared to healthy controls. The reduced CSF flow dynamics might be involved in the pathophysiology of PE in IIH and diffusion-weighted MRI can be a useful non-invasive tool to study the CSF flow dynamics within the SAS ON. Summary Idiopathic intracranial hypertension is a neurological disease, where vision loss is the most feared complication of this disorder. The pathophysiology of IIH is not fully understood but is strongly linked to a reduced uptake of CSF into the central dural sinus veins. In this study, we examined the CSF flow rates in the SAS ON and the brain in patients with IIH and PE compared to healthy controls by applying non-invasive diffusion-weighted MRI. Knowing about the flow ratio of CSF may be of clinical relevance for the treatment decisions of IIH. If medical treatment fails, surgical options for lowering the ICP pressure need to be taken into consideration. As the primary goal of treatment is to prevent the loss of vision and visual field, it is important to know whether the communication of CSF between the intracranial CSF and the CSF in the perioptic space is intact. We showed that the CSF flow velocity was decreased in IIH patients with PE compared to healthy controls. The reduced CSF flow might be involved in the pathophysiology of PE in IIH, and diffusion-weighted MRI can be a useful non-invasive tool to study the CSF flow dynamics within the SAS ON.